Streamlining verbal feedback: Reflection on a feedback research project in secondary schools (UCL Press, 2015)
This paper is a reflection on action research I conducted in two classrooms to explore the effectiveness of feedback. As a result of this project, I have changed my practice to streamline verbal feedback. Despite its transience, verbal feedback can be made far more effective if it is reduced to key points only.